Planning and Care for Children and Adolescents with Dental Enamel Defects Etiology, Research and Contemporary Management - Drummond, Bernadette K.; Drummond, Bernadette K.; Kilpatrick, Nicola.; Kilpatrick, Nicola. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
Developmental Defects of Enamel (DDE) pose a significant dental problem for children and adolescents. Affected teeth are discolored, often sensitive and prone to fracture or wear easily, increasing the risk of dental caries. Furthermore, they are often very difficult to restore because conventional dental materials do not bond effectively to the defective enamel. Clinically, affected individuals have heightened levels of dental anxiety making management challenging and stressful for the child, parent and clinician alike. This book discusses the epidemiology and etiology of DDE, including defects of both primary and permanent teeth, associated syndromes, Molar Incisor Hypomineralization and more generalized genetic defects. The structure and mechanical properties of affected enamel are discussed particularly in relation to clinical behavior. The signs and symptoms that allow accurate diagnosis are outlined and management protocols described. The clinical chapters are well illustrated, providing clear, evidence based guidelines where appropriate.  Importantly the impact of living with DDE is explored from the young person’s perspective. These insights challenge the dental profession to seek improved understanding of the condition and to develop new management strategies. Avenues for future research are identified that may help the profession rise to this challenge and to better meet the needs and expectations of future generations of children and adolescents.